2021
DOI: 10.1021/jacs.1c06780
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Strain Dynamics in Noble Metal Nanocatalysts

Abstract: The theoretical design of effective metal electrocatalysts for energy conversion and storage devices relies greatly on supposed unilateral effects of catalysts structure on electrocatalyzed reactions. Here, by using high-energy X-ray diffraction from the new Extremely Brilliant Source of the European Synchrotron Radiation Facility (ESRF-EBS) on device-relevant Pd and Pt nanocatalysts during cyclic voltammetry experiments in liquid electrolytes, we reveal the near ubiquitous feedback from various electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 46 publications
5
37
0
Order By: Relevance
“…Previous studies on Pt nanoparticle strain dynamics revealed that lattice parameter contraction is associated with desorption of various charged species from the surface. 38,39 HISPEC3000 showed no such contraction.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies on Pt nanoparticle strain dynamics revealed that lattice parameter contraction is associated with desorption of various charged species from the surface. 38,39 HISPEC3000 showed no such contraction.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…The strongest relative contraction of the lattice is found for Pt/N-V-400 followed by Pt/N-V-800 and Pt/V, respectively. Previous studies on Pt nanoparticle strain dynamics revealed that lattice parameter contraction is associated with desorption of various charged species from the surface. , HISPEC3000 showed no such contraction.…”
Section: Resultsmentioning
confidence: 87%
“…Rietveld refinement of the WAXS patterns was used to reveal the electrochemical strain dynamics (variations of the lattice constant) during three consecutive cycles of electrode polarization at 5 mV s –1 after the different conditioning steps (Figure d–f). As discussed in detail in dedicated previous contributions, , the enhanced surface-to-volume ratio of nanoparticles allows adsorption processes to be monitored by the “bulk” X-ray diffraction technique. Briefly, the lattice constant of Pt nanoparticles was found to be minimum (maximum compressive strain) at the potential of zero total charge (pztc), where the surface is (rather) free of adsorbates.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum (Pt) and Pt-based compounds are considered as the state-of-the-art electrocatalysts for ORR in the past decades, but their widespread implementation is still severely restricted by the high cost and reserve scarcity. Besides, another challenge is the durability problem of Pt, which tends to dissolve in the acidic electrolyte under long-term operating conditions. , Therefore, it is essential to rationally design higher-ORR performance and longer-lifetime Pt-based nanocatalysts with low Pt usage for fuel cells.…”
mentioning
confidence: 99%